The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00280-020-04125-w
|View full text |Cite
|
Sign up to set email alerts
|

Aloin alleviates doxorubicin-induced cardiotoxicity in rats by abrogating oxidative stress and pro-inflammatory cytokines

Abstract: Purpose Aloin, an anthraquinone present in the aloe species, possesses antiangiogenic, chemopreventive and antioxidant properties. It exerts cytotoxicity against breast cancer and ovarian cancer cell lines. These properties of aloin project it as a chemopreventive adjuvant to anticancer chemotherapy. Methods We evaluated the effect of concurrent oral administration of aloin against doxorubicin (DOX)-induced cardiotoxicity in rats. The protective effects of aloin against DOX-induced toxicity were evident as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Additionally, there is a report on the investigations of the antioxidant effects of vitamin B 1 in DOX-induced cardiotoxicity, thus this is the first study demonstrating that 7-day thiamine administration induced significant increment of antioxidants values SOD and GSH in heart tissue compared to its activity in DOX rats. The results of the previously conducted study showed depletion of antioxidative defense in heart tissue after cumulative DOX injection (Birari et al, 2020) which is in line with our findings. Also, Mohammed et al (2020) demonstrated a significantly lower level of GSH in rats` heart tissue treated with DOX compared to control.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, there is a report on the investigations of the antioxidant effects of vitamin B 1 in DOX-induced cardiotoxicity, thus this is the first study demonstrating that 7-day thiamine administration induced significant increment of antioxidants values SOD and GSH in heart tissue compared to its activity in DOX rats. The results of the previously conducted study showed depletion of antioxidative defense in heart tissue after cumulative DOX injection (Birari et al, 2020) which is in line with our findings. Also, Mohammed et al (2020) demonstrated a significantly lower level of GSH in rats` heart tissue treated with DOX compared to control.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the current study investigated the protective role of thiamine (25mg/kg i.p ) against DOX-induced cardiotoxicity in rats. This type of cardiomyopathy can be induced in experimental models through different methodologies either by single high dose or multiple lower doses of DOX applied over several days ( Birari et al, 2020 ). In the present work, DOX was administrated in a single cumulative dose (15mg/kg i.p. )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained in the present study show that treatment with vincristine causes a significant increase in the expressions of TNFα, eNOS, iNOS, and connexin 43 in the cardiac tissue of animals. Similar results have been obtained with other antitumor drugs such as doxorubicin ( Lim, 2013 ; Bin Jardan et al, 2020 ; Birari et al, 2020 ), sunitinib ( Aldemir et al, 2020 ), and cisplatin ( El-Hawwary and Omar, 2019 ). On the other hand, enhanced oxidative stress, inflammation, and upregulation of TNFα, interleukin-6 (IL-6), and interleukin-10 (IL-10) have been associated with vincristine-induced neurotoxicity of the peripheral nervous system ( Gong et al, 2016 ; Vashistha et al, 2017 ; Qin et al, 2020 ; Geisler, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…Radiation therapy is used to treat diseases such as lymphoma, breast cancer, thymoma, high and low respiratory tracts, and esophageal and gastric lesions, among others. Radiation therapy-induced heart disease, on the other hand, was most typically detected after radiotherapy for malignant tumors in the chest, particularly left breast cancer [ 158 ]. Breast cancer is one of the most frequent cancers in women, impacting women all over the world.…”
Section: Radiation Therapy-induced Cardiotoxicitymentioning
confidence: 99%